The Africans: A triple heritage : Garden of Eden in decay - Mazrui, Ali AlAmin (The Annnenberg/CPB Collection, 1986)
Identifies the problems of a continent that produces what it does not consume and consumes what it does not produce, showing Africa's struggle between economic dependency and decay. Closed captioned for the hearing impaired. Target audience: General.